BRIEF STUDY OF SUPPORTING FACTORS AND MARKETING STRATEGIES FOR MILKFISH CULTIVATION - Dadiono, Muh. Sulaiman (JURNAL LEMURU, 2023)
Milkfish cultivators in Indonesia often experience problems related to marketing strategies and supporting factors. So a brief study is needed on the marketing strategy and supporting factors for milkfish cultivation in order to provide a brief overview of milkfish cultivators in Indonesia. data collection was fully carried out by literature study. Secondary data was collected by reviewing references in the form of journals, books and online articles. Data search was carried out using the Google search engine with the keywords marketing strategy for milkfish cultivation (Chanos chanos). The data obtained were then analyzed using descriptive methods. From the results of the study, it was found that special attention was needed regarding the supporting factors for milkfish cultivation, namely the availability of seeds, environmental cleanliness, and the existence of smooth marketing channels. In addition, it is necessary to pay attention to inhibiting factors such as low productivity, low quality and quantity of seeds, not yet implemented CPIB and CBIB. Marketing strategies must keep up with the times by utilizing digital marketing such as social media platforms and market places.